2015
DOI: 10.1007/s11581-015-1397-z
|View full text |Cite
|
Sign up to set email alerts
|

Study on LiFe1 − x Sm x PO4/C used as cathode materials for lithium-ion batteries with low Sm component

Abstract: LiFe 1−x Sm x PO 4 /C cathode materials were synthesized though a facile hydrothermal method. Compared with high-temperature solid-phase sintering, the method can allow for the fabrication of low Sm content (2 %), a scarce and expensive rare earth element, while the presence of an optimized carbon coating with large amount of sp 2 -type carbon sharply increases the material's electrochemical performance. The high-rate dischargeability at 5 C, as well as the exchange current density, can be increased by 21 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Considering the large radius, high charge and strong self-polarization ability of rare earth (RE) ions, therefore, it naturally raises an interesting issue: whether RE-doping will bring dramatic changes to LIBs or not. In recent years, experimental studies have been made in RE-decorated electrode materials such as LiCoO 2 , LiMn 2 O 4 , LiFePO 4 , and LiNi 1/3 Co 1/3 Mn 1/3 O 2 , etc. For example, Yang and co-workers reported that the lattice parameters increase due to the large radius of RE ions for the LiMn 2– x RE x O 4 ( x ≤ 0.01, RE = Y, Nd, Gd, Ce) systems.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the large radius, high charge and strong self-polarization ability of rare earth (RE) ions, therefore, it naturally raises an interesting issue: whether RE-doping will bring dramatic changes to LIBs or not. In recent years, experimental studies have been made in RE-decorated electrode materials such as LiCoO 2 , LiMn 2 O 4 , LiFePO 4 , and LiNi 1/3 Co 1/3 Mn 1/3 O 2 , etc. For example, Yang and co-workers reported that the lattice parameters increase due to the large radius of RE ions for the LiMn 2– x RE x O 4 ( x ≤ 0.01, RE = Y, Nd, Gd, Ce) systems.…”
Section: Introductionmentioning
confidence: 99%
“…Other ionic doping processes have been developed for enhancing the electrochemical performances of Li‐ion batteries, including doping of Mg, [ 134 ] Mn, [ 135 ] Zn, Co, Pt, Sm, [ 136 ] and other rare earth element [ 137 ] in LiFePO 4 . [ 138 ] Co doping had been studied to increase the electrical conductivity and the redox potential of Fe 2+/3+ , thus, increasing the discharge plateau.…”
Section: Lattice Substitutionmentioning
confidence: 99%
“…These values are consolidated in Table 1 and displayed in Figure 2 (a) & (b). Doping effect will sometime increase or decrease lattice parameters depending on the nature of doping ion and amount of doping [5,10,11,13,14]. It is seen that doping of lanthanum does not change the crystal structure but decreases the lattice parameter along a-axis and increases along c-axis in LiNiPO4 as the position of Li + in the lattice is partially replaced by La 3+ , which is favorable for the transmission of Li ions along c-axis [11].…”
Section: A Xrd Analysismentioning
confidence: 99%